Pistachio hull extract as a natural antioxidant incorporated into pistachio paste: Antioxidant activity and oxidative stability - Hoda Farrokhi; Mohammad Hadi Eskandari; Ahmad Shakerardekani; Mohammad Taghi Golmakani; Mehrdad Niakousari (Applied Food Research)
Pistachio hull (PH) and testa (TS), the primary pistachio wastes during production of paste, fresh kernel, and un-refined oil, were extracted for their valuable bioactive compounds using a mixture of ethanol and water (1:1, v/v) through conventional (CNE), ohmic heating-assisted (OHE), and atmospheric cold plasma-assisted (CAP) extraction methods. The total phenol content (TPC), total flavonoid content (TFC), and antioxidant activity (AA) of the extracts were determined. The optimum extract was selected according to its highest values of TPC, TFC, and AA. The findings indicate that these values for PH extracts are higher than those of TS extracts. The extracts by OHE and CAP exhibited higher respective properties than the extracts obtained through CNE. The highest values of TPC (20.51 mg GAE/g), TFC (484.10 mg quercetin/g extract), and AA (85.86 %) correspond to the extracts obtained from PH through extraction using the OHE method. This extract (PH-OHE) was selected as the “optimum extract” and was incorporated into pistachio paste (PP). The resulting paste (PPE) was examined for its oxidative stability through assessment of acid, peroxide, anisidine values, induction period (IP), fatty acid profile, and color indexes during 25 days of accelerated storage at 60 °C. The lowest acid (2.21 versus 5.74 % oleic acid), peroxide (26.60 versus 102.47 meq O2/kg), and anisidine (6.17 versus 17.43) values, and higher IP (8.5 versus 4.32 h) were achieved for the paste containing optimum extract. Linoleic acid was efficiently maintained in PPE (24.30 %) compared to CPP (control sample, no extract) (18.64 %). Moreover, PPE’s a* value was -3.02 versus 1.42 for the CPP sample, indicating maintenance of beautiful green color in a sample containing the extract. This study reveals that PH-OHE extract holds practically most of the characteristics of a “natural efficient antioxidant”.